Microwave prostate cancer detection with three dimensional FDTD analysis - 273431 Senthilkumar Ramasamy; Akram Gamelseed Abdalla Mukhtar, supervisor; Fakulti Kejuruteraan Elektrik (2007)
Project Paper (Sarjana Muda kejuruteraan (Elektrik - Elektronik)) - Universiti Teknologi Malaysia, 2007